How to optimize hepatitis C virus treatment impact on life years saved in resource‐constrained countries. Issue 1 (27th February 2015) - Obach, Dorothée; Yazdanpanah, Yazdan; Esmat, Gamal; Avihingsanon, Anchalee; Dewedar, Sahar; Durier, Nicolas; Attia, Alain; Anwar, Wagida A.; Cousien, Anthony; Tangkijvanich, Pisit; Eholié, Serge Paul; Doss, Wahid; et al.
<x xml:space="preserve">Abstract</x> In resource‐constrained countries where the prevalence of hepatitis C virus (HCV) disease is usually high, it is important to know which population should be treated first in order to increase treatment effectiveness. The aim was to estimate the effectiveness of different HCV treatment eligibility scenarios in three different countries. Using a Markov model, we estimated the number of life‐years saved (LYS) with different treatment eligibility scenarios according to fibrosis stage (F1‐F4 or F3‐4), compared to base case (F2‐F4), at a constant treatment rate, of patients between 18 and 60 years of age, at stages F0/F1 to F4, without liver complications or coinfections, chronically infected by HCV, and treated with pegylated interferon (IFN)/ribavirin or more‐efficacious therapies (i.e. IFN free). We conducted the analysis in Egypt (prevalence = 14.7%; 45, 000 patients treated/year), Thailand (prevalence = 2.2%; 1, 000 patients treated/year), and Côte d'Ivoire (prevalence = 3%; 150 patients treated/year). In Egypt, treating F1 patients in addition to ≥F2 patients (SE1 vs. SE0) decreased LYS by 3.9%. Focusing treatment only on F3‐F4 patients increased LYS by 6.7% (SE2 vs. SE0). In Thailand and Côte d'Ivoire, focusing treatment only on F3‐F4 patients increased LYS by 15.3% and 11.0%, respectively, compared to treating patients ≥F2 (ST0 and SC0, respectively). Treatment only for patients at stages F3‐F4 with IFN‐free therapies would increase LYS by 16.7% versus SE0 in Egypt, 22.0% versus ST0 in Thailand, and 13.1% versus SC0 in Côte d'Ivoire. In this study, we did not take into account the yearly new infections and the impact of treatment on HCV transmission. Conclusion: Our model‐based analysis demonstrates that prioritizing treatment in F3‐F4 patients in resource‐constrained countries is the most effective scenario in terms of LYS, regardless of treatment considered. (Hepatology 2015;62:31‐39)